Performance of real‐world functional vision tasks by blind subjects improves after implantation with the Argus® II retinal prosthesis system. (7th September 2016) - Dagnelie, Gislin; Christopher, Punita; Arditi, Aries; da Cruz, Lyndon; Duncan, Jacque L; Ho, Allen C; Olmos de Koo, Lisa C; Sahel, José‐Alain; Stanga, Paulo E; Thumann, Gabriele; Wang, Yizhong; Arsiero, Maura; et al.
Abstract: Background: The main objective of this study was to test Argus II subjects on three real‐world functional vision tasks. Design: The study was designed to be randomized and prospective. Testing was conducted in a hospital/research laboratory setting at the various participating centres. Participants: Twenty eight Argus II subjects, all profoundly blind, participated in this study. Methods: Subjects were tested on the three real‐world functional vision tasks: Sock Sorting, Sidewalk Tracking and Walking Direction Discrimination task Main Outcome Measures: For the Sock Sorting task, percentage correct was computed based on how accurately subjects sorted the piles on a cloth‐covered table and on a bare table. In the Sidewalk Tracking task, an 'out of bounds' count was recorded, signifying how often the subject veered away from the test course. During the Walking Direction Discrimination task, subjects were tested on the number of times they correctly identified the direction of testers walking across their field of view. Results: The mean percentage correct OFF versus ON for the Sock Sorting task was found to be significantly different for both testing conditions ( t ‐test, P < 0.01). On the Sidewalk Tracking task, subjects performed significantly better with the system ON than they did with the system OFF ( t ‐test, P < 0.05). Eighteen (18) of 27 subjects (67%) performed above chance with the system ON, and 6 (22%) did so with system OFF on the Walking Direction Discrimination task. Conclusions: Argus II subjects performed better on all three tasks with their systems ON than they did with their systems OFF.